Case Report: Late spontaneous orbital subperiosteal hematoma after endoscopic sinonasal tumor resection. (March 2023) - Usmani, Eiman; Shapira, Yinon; Patel, Sandy; Psaltis, Alkis J.; Selva, Dinesh
Abstract: Introduction and importance: We report a case of spontaneous subperiosteal orbital hematoma many years after endoscopic sinonasal resection of malignancy. Case presentation: A 50-year-old female with a six-year history of endoscopic sinonasal resection of a poorly differentiated neuroendocrine tumor presented with two days of worsening frontal headache and left periocular swelling. A subperiosteal abscess was initially suspected on CT; however, MRI sequences revealed changes consistent with the diagnosis of hematoma. A conservative approach was justified based on the clinico-radiologic features. Progressive clinical resolution was noted over three weeks. Two monthly follow-up MRI revealed resolution of the orbital findings with no features to indicate recurrence of malignancy. Clinical discussion: Subperiosteal pathologies can be clinically challenging to differentiate. Differing radiodensities on CT may help differentiate between them but is not always reliable. MRI is more sensitive and is the preferred imaging modality. Conclusion: Spontaneous orbital hematomas are self-resolving, and surgical exploration may be avoided in the absence of complications. Therefore, it is beneficial to recognize it as a potential late complication of extensive endoscopic endonasal surgery. Characteristic features on MRI can aid diagnosis. Highlights: Similar clinical presentations between subperiosteal orbital hematoma and abscess can make diagnosis challenging Familiarity with radiological differences may help secure the correct diagnosis and evade surgical exploration Subperiosteal pathologies are well-defined lenticular or inverted "D" shaped lesions on imaging. Differing radiodensities on CT may help differentiate between subperiosteal pathologies. MRI is more sensitive and is the preferred imaging modality. Presentation of hematoma on MRI varies depending on the stage of the bleed